2016
DOI: 10.1097/md.0000000000004360
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ambulatory function and clinical factors in hemiplegic patients with intact single lateral corticospinal tract

Abstract: To define the relationship between the complete destruction of 1 lateral corticospinal tract (CST), as demonstrated by diffusion tensor imaging (DTI) tractography, and ambulatory function 6 months following stroke.Twenty-six adults (17 male, 9 female) with poststroke hemiplegia who were transferred to the physical medicine and rehabilitation department. Participants underwent DTI tractography, which showed that 1 lateral CST had been clearly destroyed.Functional ambulation classification (FAC) scores at admiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Further, functional imaging studies showed activation of the ipsilateral sensorimotor cortex; ipsilateral parietal region, and bilateral pre-frontal regions in stroke patients tasked with a finger-thumb opposition task (Marshall et al, 2000); again, this implicates the activation of the ipsilateral aspect, but also recruitment of additional cortical areas to regain function over time. Additional, similar studies in patients over the course of their recovery report recruitment of the ipsilateral, lateral corticospinal tract and reogranisation of the motor cortex in the unlesioned hemisphere (Ahn et al, 2006;Hong et al, 2016;Peters et al, 2021;Yeo & Jang, 2012). However, others report that these ipsilateral contributions may be overstated and that they may even be maladaptive (Fregni & Pascual-Leone, 2006;Madhavan et al, 2010;Zaaimi et al, 2012).…”
Section: Descending Tractsmentioning
confidence: 93%
“…Further, functional imaging studies showed activation of the ipsilateral sensorimotor cortex; ipsilateral parietal region, and bilateral pre-frontal regions in stroke patients tasked with a finger-thumb opposition task (Marshall et al, 2000); again, this implicates the activation of the ipsilateral aspect, but also recruitment of additional cortical areas to regain function over time. Additional, similar studies in patients over the course of their recovery report recruitment of the ipsilateral, lateral corticospinal tract and reogranisation of the motor cortex in the unlesioned hemisphere (Ahn et al, 2006;Hong et al, 2016;Peters et al, 2021;Yeo & Jang, 2012). However, others report that these ipsilateral contributions may be overstated and that they may even be maladaptive (Fregni & Pascual-Leone, 2006;Madhavan et al, 2010;Zaaimi et al, 2012).…”
Section: Descending Tractsmentioning
confidence: 93%
“…Despite the importance of the crossed lateral corticospinal tract for lower limb movement and recovery after stroke, other studies question the importance of this tract. Functional movements such as walking are present in individuals with chronic stroke even when the crossed lateral corticospinal tract to the paretic limb is completely destroyed (Ahn et al., 2006; Cho et al., 2012; Hong et al., 2016). The extent to which a stroke lesion impacts the crossed lateral corticospinal tract is not predictive of walking speed (Dawes et al., 2008) or change in walking speed with treadmill rehabilitative training in individuals with chronic subcortical stroke (Seo et al., 2014).…”
Section: Crossed (Contralateral) Lateral Corticospinal Tractmentioning
confidence: 99%